2014
DOI: 10.1007/s12311-014-0627-7
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Paper: The Role of the Cerebellum in Perceptual Processes

Abstract: Various lines of evidence accumulated over the past 30 years indicate that the cerebellum, long recognized as essential for motor control, also has considerable influence on perceptual processes. In this paper, we bring together experts from psychology and neuroscience, with the aim of providing a succinct but comprehensive overview of key findings related to the involvement of the cerebellum in sensory perception. The contributions cover such topics as anatomical and functional connectivity, evolutionary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
326
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 392 publications
(352 citation statements)
references
References 244 publications
(307 reference statements)
20
326
0
6
Order By: Relevance
“…Cerebellum is also involved in pain perception (Moulton et al , 2010, Baumann et al , 2015, and may have altered functional connectivity in migraineurs (Chen et al , 2015). A study of brain network connectivity during induced migraine attacks found decreased resting-state functional connectivity, measured by fMRI, between cerebellum and the "default mode network" hours before migraine pain was experienced, which may suggest lack of cerebellar nociceptive modulation (Amin et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellum is also involved in pain perception (Moulton et al , 2010, Baumann et al , 2015, and may have altered functional connectivity in migraineurs (Chen et al , 2015). A study of brain network connectivity during induced migraine attacks found decreased resting-state functional connectivity, measured by fMRI, between cerebellum and the "default mode network" hours before migraine pain was experienced, which may suggest lack of cerebellar nociceptive modulation (Amin et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has emerged that internal models play a role in non-motor functions and that the cerebellum plays a role in perceptual processes [8].…”
Section: Cerebellar Calibration Of Audio-motor Mapmentioning
confidence: 99%
“…There has been considerable progress in cerebellar research over the past decade and an increasing number of studies have reported the function of the cerebellum in sensory and perceptual mechanisms [8][9][10][11] and in components of the motor hierarchy, which are separate from mere motor control [12,13].…”
Section: Introductionmentioning
confidence: 99%